Succinate Facilitates CD4+ T Cell Infiltration and CCL1 Production to Promote Myofibroblast Activation and Renal Fibrosis in UUO Mice - Tao Y; Zhang W; Liu D; Cao H; Yi X; Deng X; Li P; Shen X; Zhou H (Journal of Inflammation Research, 2025)
Yuandong Tao,1,* Wei Zhang,2,* Dehong Liu,3,* Hualin Cao,4 Xiaoyu Yi,1 Xiangling Deng,1 Pin Li,1 Xiaoli Shen,1 Huixia Zhou1 1Department of Pediatric Urology, The Seventh Medical Center of Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Department of Urology, Quanzhou First Hospital Affiliated to Fujian Medical University, Quanzhou, People’s Republic of China; 3Department of Pediatric Surgery, Ruijin Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, People’s Republic of China; 4Department of Urology, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huixia Zhou, Email huixia99999@163.com Dehong Liu, Email ldh11301@rjh.com.cnAim: Obstructive nephropathy is a leading cause of kidney injury and fibrosis, which is always associated with metabolic aberrations and chronic inflammation. Succinate is an important intermediate metabolite involved in inflammatory responses and various diseases. However, the precise pathogenic mechanisms of succinate in obstructive nephropathy remain to be elucidated.Methods: Succinate was supplemented in the drinking water to study its impact on the pathogenesis of obstructive nephropathy induced by unilateral ureteral obstruction (UUO) in mice. Kidney fibrosis, injury, inflammatory cytokines, and infiltrated immune cells were analyzed. Transcriptome analysis and in vitro studies were performed to study the cellular and molecular mechanisms by which succinate regulates CD4+ T cells and renal fibrosis.Results: Kidney proteomics revealed that the tricarboxylic acid (TCA) cycle and mitochondrial dysfunction were the hallmarks of obstructive nephropathy. Succinate was significantly accumulated in the obstructed kidneys. Succinate supplementation promoted UUO-induced renal fibrosis, injury, and inflammation. Moreover, succinate facilitated renal infiltration of CD4+ T cells by upregulating the T-cell chemokines CXCL9 and CXCL10. Transcriptome analysis suggested that succinate promoted CD4+ T cell activation and induced the production of CCL1, which mediated the transition of fibroblasts to myofibroblasts through the ERK signaling pathway. Recombinant CCL1 treatment promoted UUO-induced renal fibrosis and inflammation.Conclusion: Our study uncovers the important role of succinate in mediating T-cell response that orchestrates the pathogenesis of obstructive nephropathy. Targeting succinate accumulation may be a therapeutic strategy for the treatment of obstructive nephropathy. Keywords: obstructive nephropathy, renal fibrosis, succinate, CD4+ T cell, CCL1